Large-scale comparative metagenomics of Blastocystis, a common member of the human gut microbiome - Beghini, Francesco; Pasolli, Edoardo; Truong, Tin Duy; Putignani, Lorenza; Cacciò, Simone M; Segata, Nicola (The ISME Journal, 2017)
The influence of unicellular eukaryotic microorganisms on human gut health and disease is still largely unexplored. Blastocystis spp. commonly colonize the gut, but its clinical significance and ecological role are currently unsettled. We have developed a high-sensitivity bioinformatic pipeline to detect Blastocystis subtypes (STs) from shotgun metagenomics, and applied it to 12 large data sets, comprising 1689 subjects of different geographic origin, disease status and lifestyle. We confirmed and extended previous observations on the high prevalence the microrganism in the population (14.9%), its non-random and ST-specific distribution, and its ability to cause persistent (asymptomatic) colonization. These findings, along with the higher prevalence observed in non-westernized individuals, the lack of positive association with any of the disease considered, and decreased presence in individuals with dysbiosis associated with colorectal cancer and Crohn’s disease, strongly suggest that Blastocystis is a component of the healthy gut microbiome. Further, we found an inverse association between body mass index and Blastocystis , and strong co-occurrence with archaeal organisms ( Methanobrevibacter smithii ) and several bacterial species. The association of specific microbial community structures with Blastocystis was confirmed by the high predictability (up to 0.91 area under the curve) of the microorganism colonization based on the species-level composition of the microbiome. Finally, we reconstructed and functionally profiled 43 new draft Blastocystis genomes and discovered a higher intra subtype variability of ST1 and ST2 compared with ST3 and ST4. Altogether, we provide an in-depth epidemiologic, ecological, and genomic analysis of Blastocystis , and show how metagenomics can be crucial to advance population genomics of human parasites.